Penerapan Terapi Nonfarmakologis Metode Sitz Bath Pada Ibu Postpartum Fisiologi Dengan Nyeri Episiotomi - Novira, Iva Annisha; Inayati Al Bayani, Melati; Utami, Kusniyati (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2021)
Every mother undergoing childbirth who has an injury to the perineum will feel pain, either a wound made like an episiotomy or a spontaneous tear wound. Pain management can be done nonpharmacologically, one of them is the Sitz Bath method, which is a safer choice for postpartum mothers because it reduces risks and side effects and is in line with physiological processes. The purpose of this study is to describe nursing care using the Sitz Bath method in reducing the intensity of episiotomy pain in postpartum physiology mothers. With a case study approach on primigravidian physiologi postpartum Results indicated that implementation of the Sitz Bath to reduce the intensity of pain is influenced by the level of knowledge of the mother, mobilization of the mother during postpartum, and support from the family, as well as support from health workers to provide knowledge. After 4 times Sitz Bath metho applied, there was a decrease in pain intensity in the perinum wound of postpartum physiology primigravida. It is expected that the other researcher explore the other intervention to reduce episiotomy pain.